Cryopreservation Challenges and Cryoprotectant Efficacy in Cyprinodon variegatus Embryos - Santos, Guillermo Manuel; Rocha, Francisco; Paredes, Estefanía (Problems of Cryobiology and Cryomedicine, 2024)
Probl Cryobiol Cryomed 2024; 34(4):304